2019
DOI: 10.1002/anie.201811630
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Oxidation and Depolymerization of α,γ‐Diol‐Protected Lignin

Abstract: Lignin oxidation offers ap otential sustainable pathway to oxygenated aromatic molecules.H owever,c urrent methods that use real lignin tend to have low selectivity and ay ield that is limited by lignin degradation during its extraction. We developed stoichiometric and catalytic oxidation methods using 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) as oxidant/catalyst to selectively deprotect the acetal and oxidizethe a-OH into aketone.The oxidized lignin was then depolymerized using af ormic acid/sodium form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 28 publications
3
81
0
Order By: Relevance
“…It has been demonstrated that the oxidation of benzylic hydroxyl could both weaken the C β −O bonds and suppress the condensation reactions induced by the reactive benzylic carbocations (C α + ) . The earliest work on the depolymerization of oxidized lignin was proposed by Stahl group in 2013 and 2014 (Figure ).…”
Section: Other Strategies For Improving the Monomer Yields And Potentmentioning
confidence: 99%
“…It has been demonstrated that the oxidation of benzylic hydroxyl could both weaken the C β −O bonds and suppress the condensation reactions induced by the reactive benzylic carbocations (C α + ) . The earliest work on the depolymerization of oxidized lignin was proposed by Stahl group in 2013 and 2014 (Figure ).…”
Section: Other Strategies For Improving the Monomer Yields And Potentmentioning
confidence: 99%
“…In the subsequent experiments we turned our attention toward the photochemical degradationo f2-phenoxy-1-phenylethanol (3), as shown in Figure S7 (Supporting Information). From the GC-MSa nalysis, 3 first converted to ketone( 1), and then underwent similarc leavage of CÀC/CÀOt o1.F urther,a ttention was paid to the photochemical degradation of a-O-4 types of lignin-derived aryl ethers, benzyl phenyle ther (4), and 4-(benzyloxy)phenol (5), as shown in Figure S8 (Supporting Information).F rom the results, aromatic aldehydes originating from oxidative processes were detected, indicatingt he implementation prospect of the photochemical system to CÀO bond cleavage in lignin a-O-4 linkages.…”
Section: Photodegradation Of Other Lignin-derivedaryl Ethers and Alkamentioning
confidence: 99%
“…[2] However,u ntil now, this large amount of lignin has been underexploited chemically,a nd less than 5% of lignin is used as low-grade fuels or concrete additives. [4] In addition, lignin-derived compounds containing a b-aryl ether bond, the most abundant linkageo f native lignin, [5] are often adopted to study lignin conversion processes. [4] In addition, lignin-derived compounds containing a b-aryl ether bond, the most abundant linkageo f native lignin, [5] are often adopted to study lignin conversion processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a beech butanosolv lignin was prepared according to previous reports [18] and the oxidation of the primary alcohol groups to aldehydes in Scheme 1. Previously reported two-step oxidative approaches to lignin depolymerisation via a) secondary [6][7][8][9][10][11] or b) primary alcohol [12][13][14] oxidation of native type β-aryl ether linkages lignin compared to this work c) employing selective oxidation and NHC catalysis for the depolymerisation of butanosolv lignin βaryl ether linkages. the β-aryl ether linkages was attempted using the biphasic TEMPO/NCS catalytic system developed by Einhorn et al [22] In contrast to our previous reports on the direct TEMPO-catalysed oxidation of this alcohol to carboxylic acids, [23] attempts to perform this reaction on the butanosolv lignin failed to provide the expected aldehyde product.…”
Section: Selective Depolymerisation Of γ-Oxidised Lignin Via Nhc Catamentioning
confidence: 99%